2022
DOI: 10.3389/fmed.2022.1057165
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of optical coherence tomography angiography metrics during hemodialysis procedures: A pilot study

Abstract: Background and aimsThe observation of optical microcirculation gives us an extraordinary way to directly assess in vivo the responses of human circulation to stress stimuli. We run a pilot study to analyze optical coherence tomography angiography (OCT-A) metrics at determined time-points during a hemodialysis (HD) session to understand how these metrics gradually change and to evaluate possible correlations with patients’ characteristics.MethodsAfter the eligibility screening, 15 patients (23 eyes) were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…This is in line with the findings by Shin et al, who did not see any differences in FD of the SCP and DCP before and after HD sessions, but who describe the FD of the CC to decrease significantly after the treatment [12]. Further trials have generated different findings, as they report a reduction of FD at the level of the DCP and an increase in FD in the SCP for hypotensive patients [14]. Fursova et al described a decrease in the circularity index of the FAZ associated with HD treatment [32].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in line with the findings by Shin et al, who did not see any differences in FD of the SCP and DCP before and after HD sessions, but who describe the FD of the CC to decrease significantly after the treatment [12]. Further trials have generated different findings, as they report a reduction of FD at the level of the DCP and an increase in FD in the SCP for hypotensive patients [14]. Fursova et al described a decrease in the circularity index of the FAZ associated with HD treatment [32].…”
Section: Discussionsupporting
confidence: 89%
“…It allows for the non-invasive visualization of blood vessels through the detection of moving blood cells and is being discussed to act as a possible surrogate biomarker to estimate microvascular status [11]. To date, only a limited number of studies have investigated capillary changes in patients receiving HD using OCTA [12][13][14]. These trials have assessed short-term changes in OCTA parameters either before and after HD sessions, or over the course of individual HD sessions, focusing on relative alterations between same-day measurements, rather than on the overall effect of HD on ESRD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we have demonstrated that higher MBG plasma levels are associated with a lower risk of intradialytic hypotensive events in patients undergoing hemodialysis [ 20 , 101 , 102 ], who are particularly considered at risk of hypotension. Indeed, about 30% of hemodialysis sessions are characterized by severe symptomatic intra-dialysis hypotension, influencing the morbidity and mortality of patients in chronic treatment.…”
Section: Marinobufagenin and Chronic Kidney Diseasementioning
confidence: 99%